Percepción de los efectos (económicos, financieros, sociales) de incentivos referentes a las devoluciones del IVA y discapacitados en el sector exportador en el período 2011-2013 del Distrito Metropolitano de Quito - Pérez Guerra, Cristian Xavier (2014)
The Ecuadorian State through the Service of Internal Rents SRI, grants tributary benefits to the exporter sector, such as the refund of the Tax to the Added Value IVA in purchases of goods and services that are used for the elaboration of the final product to export and deduction in the Tax to the Rent for the recruiting of disabled staff, with the purpose of contributing from a socioeconomic way to the country. The companies exporters that make the steps of refund of IVA generate a financial impact when obtaining liquidity and in that way to emit several payments, they also generate a tributary impact when declaring and to deduce for half the credit note emitted by the SRI their monthly or annual taxes. In some cases these steps are carried out by the plant personnel and others for specialist suppliers in the tributary topic creating an additional expense to the company.